Chronic copper poisoning in a sheep - Cecco, Bianca S. de; Molossi, Franciéli A.; Mello, Lauren S. de; Bianchi, Matheus V.; Pavarini, Saulo P. (Brazilian Journal of Veterinary Pathology, 2022)
A one-year-old female Texel sheep had anorexia and jaundice. After one day, the clinical condition progressed to lethargy, lateral recumbency, and death within hours. The sheep was part of a flock of 20 housed indoors and received an increasing amount of feed (specific for sheep) for the last two months.